ANALISIS PERUBAHAN PENGGUNAAN LAHAN MENJADI LAHAN TERBANGUN PASCA PERPINDAHAN IBUKOTA KABUPATEN SUKABUMI DI WILAYAH TELUK PALABUHANRATU - Yuda Pringgo Bayusukmara; Baba Barus; Akhmad Fauzi (Diponegoro University, 2019)
The determination of the Capital of Sukabumi Regency had implications on Palabuhanratu Bay area in terms of the physical area marked by the change of land use. This research was begun by analyzing land use change using Landsat imagery. Markov Chain and CA-Markov Chain method were used to predict land use change. Prospective Structural Analysis assume that the future is different from the past and is not imposed, but can be built. MICMAC method were used to determine key variables in influencing the change of land use into built-area. The results showed that in the period of post-relocation, the built-up area had a significant increase than the period of pre-relocation. The prediction results of 2030 indicate the type of land use which had a significant decrease from 2016-2030 were beach sand and waterbodies. The type of land use which had higher increase was built-up area and shrub. The key variables that influence the change of land use into built-up area in Palabuhanratu Bay area in the present situation are distance to the city center, Regional Spatial Plan policy, and slope. In future situation, variables such as distance to cities, Regional Spatial Plan policy, and the proportion of paddy field would be the key variables in influencing the change of land use into built-up area.